Analyzing factors influencing cooperativeness using the Prisoner’s Dilemma - Nagyné Kiszlinger, Henrietta; Zilizi, Rozália; Nagy, István (Acta Scientiarum Socialium, 2011)
The authors analyzed the factors that can influence cooperativeness. Altogether 102 participants were asked to play the Prisoner’s Dilemma game as a measurement of cooperativeness (those people who did not confess were considered cooperative). The participants were asked about their sex, age, education, and occupation. The results were analyzed using a Chi-square test. Probably due to the relatively small sample size, none of the investigated factors affected the participants’ answer. However, for education and occupation clear tendencies were found showing that higher education and intellectual activity coincided with a higher tendency toward cooperation.
Keywords: Prisoner’s Dilemma; cooperative and competitive behaviour